Robust cascade control of a deployable cable-driven robot. (15th July 2019) - Khalilpour, S.A.; Khorrambakht, R.; Taghirad, H.D.; Cardou, Philippe
Highlights: Dynamic formulation of a deployable cable-driven robot considering the actuator models was derived. A novel control topology based on a cascade structure was proposed. Stability of the system as a whole was analyzed via Lyapunov direct method. The novel method was implemented on a deployable cable-driven robot called ARASCAM. Results showed that our controller achieved a suitable tracking performance. Abstract: In this paper, we derive the dynamic formulation of a deployable cable-driven robot that considers models of the actuator and power transmission systems, and we investigate the challenges of structural uncertainty. To accommodate the inherent uncertainty of the system, we propose a proper control topology based on a cascade structure. The inner loop of the structure controls the cable forces, and the outer loop tracks the precise position of the robot's end-effector. For the design of the outer loop controller, we propose a robust sliding mode controller with a stability analysis that is based on the Lyapunov direct method. The main contribution of this paper is to analyze the stability of the system as a whole considering both the inner and outer loop controllers. Finally, in order to illustrate the performance of the proposed controller, we present the results of an experiment on a deployable suspended cable-driven robot, which shows the effectiveness of the proposed controller in the presence of the inherent uncertainties of the system.